Modified fiber mining filling material and preparation method thereof

Through the dual modification technology of plasma treatment and silane coupling agent, the fibers are modified, which solves the problem of poor dispersion of fiber cementing and filling materials, and significantly improves the compressive strength and durability of the material.

CN119528526AActive Publication Date: 2025-02-28XUCHEN MINING TECH DEV (XUZHOU) CO LTD

Patent Information

Application Number
CN202411790252.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Fiber cemented filling materials have poor dispersion problems in mine filling applications, which leads to a decrease in the mechanical properties and durability of the materials and increases the risk of material damage.

Method used

The fiber is modified by dual modification technology of plasma treatment and silane coupling agent, which increases the functional groups on the fiber surface and improves its dispersion in the cementitious agent.

Benefits of technology

The dispersion of fibers in the filling material is significantly improved, the compressive strength and compressive strength retention rate of the material are improved, and the durability and reliability of the structure are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

According to the modified fiber mining filling material and the preparation method thereof provided by the invention, through a dual modification technology of plasma treatment and a silane coupling agent, the uniform dispersity of fibers in a cementing agent is enhanced, and the properties such as rapid hardening, early strength and compressive strength retention rate of the filling material are remarkably improved. The filling material comprises cement clinker, solid waste, a retarder, an early strength agent, modified fibers, an accelerator, gypsum, a water reducing agent, a suspending agent and other raw materials, the modified fibers are treated through specific steps, surface functional groups are increased, and the compatibility and binding power of the modified fibers and a cementing agent are improved. The filling material disclosed by the invention has the advantages of good transportability, simplicity and convenience in construction, low cost and environmental protection characteristic, conforms to the development trend of green mining industry, is particularly suitable for being applied to mine filling and supporting, and has wide application prospects and social and economic values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of mining filling materials, and in particular relates to a modified fiber mining filling material and a preparation method thereof. Background Art

[0002] From the perspective of mine filling mining technology and application, the requirements for filling materials are as follows: the initial setting time is adjustable, the final setting time needs to be short, the material can flow by itself or be pumped, and the filling body has high strength in the later stage. Common filling materials include fly ash, gypsum, lime, cement, coal gangue, slag and other materials. Traditional filling mines mainly increase the strength of the filling body by increasing the content of cementitious materials in the filling slurry, but this will increase the filling cost. At the same time, the excessive amount of cementitious materials will cause the filling body to increase in brittleness, sudden damage and instability. Problems are prominent. Furthermore, the large-scale use of cement, slag and other materials as mining filling materials will increase the density of the material, thereby increasing the auxiliary transportation volume, which is not conducive to the transportation of materials.

[0003] Fiber bonding filling technology has been widely used in the field of mining filling due to its unique advantages. By combining fiber materials with binders, the overall mechanical properties of the material, including compressive strength and impact resistance, can be significantly improved. The addition of fibers can effectively disperse stress and reduce stress concentration inside the material, thereby improving the durability and reliability of the structure. Fiber bonding filling materials have good crack control capabilities. When the structure is subjected to load, the presence of fibers can delay the expansion of cracks and increase the toughness of the material, so that the structure exhibits better stability and safety when subjected to impact or cyclic loads. Compared with traditional reinforcement methods, fiber bonding filling technology can not only reduce the amount of materials used and reduce engineering costs, but also has a simple construction process, which can shorten the construction period and improve engineering efficiency. With the increasing requirements for sustainable development and environmental protection, fiber bonding filling technology has received more and more attention due to its lower environmental impact and resource consumption.

[0004] However, fiber bonding filling technology encounters the problem of poor dispersion during mine filling application, which is mainly due to the difficulty in achieving uniform distribution of fiber materials in the binder. When the fiber and binder are not mixed evenly, the mechanical properties and durability of the material will be affected, resulting in a decrease in the stability and reliability of the overall structure. Poor dispersion causes the fibers to form aggregation areas in the material, causing stress concentration and increasing the risk of damage to the material when subjected to stress. At the same time, the aggregation of fibers may also increase the porosity inside the material, reducing the density and impermeability of the material. Therefore, improving the dispersion of fibers in the binder is the key to ensuring the successful application of fiber bonding filling technology.

[0005] In order to improve the dispersion of fibers, some technical means can be used, such as using a mixer for full mixing, or using special mixing processes and equipment to ensure that the fibers are evenly distributed in the binder. At the same time, choosing the right fiber length and type, as well as optimizing the ratio and properties of the binder, are also effective ways to improve dispersion. Through these measures, the overall performance and application effect of fiber-bonded filling materials can be significantly improved.

[0006] In order to solve the problem of uneven dispersion of fiber materials in binders, the present invention provides a method for modifying fibers, in which the fiber surface is etched by an acidic solution, and ultrasonic oscillation is used to relax and creep the molecular chains in the fiber. The fiber is then treated with plasma and a silane coupling agent to increase functional groups such as carboxyl and hydroxyl groups on the fiber surface, which is beneficial for uniform distribution of the fiber in the binder, improves the compressive strength and compressive strength retention rate after filling, and thus improves the durability and reliability of the structure. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a modified fiber mining filling material and a preparation method thereof, which adopts a dual modification technology of plasma treatment and silane coupling agent to promote the uniform dispersion of fibers in the binder, so that the filling material has better excellent properties such as quick setting, early strength, and high compressive strength retention rate, and is particularly suitable for applications in mine filling support.

[0008] The present invention relates to a modified fiber mining filling material, which comprises the following raw material components by weight: 35-75 parts of cement clinker, 10-20 parts of solid waste, 0.1-3 parts of retarder, 1-5 parts of early strength agent, 20-45 parts of modified fiber, 5-15 parts of accelerating agent, 10-20 parts of gypsum, 0.1-3 parts of water reducing agent and 0.5-5 parts of suspending agent.

[0009] The cement clinker includes at least one of aluminate cement clinker, sulphoaluminate cement clinker, ferroaluminate cement clinker and fluoroaluminate cement clinker.

[0010] The solid waste includes at least one of steel slag powder, copper slag powder, fly ash, carbide slag and coal gangue.

[0011] The retarder includes at least one of sodium gluconate, borax or citric acid.

[0012] The early strength agent includes at least one of calcium chloride, calcium sulfate, water glass or triethanolamine.

[0013] The accelerating setting agent includes at least one of sodium aluminate, sodium sulfate or sodium carbonate.

[0014] The gypsum includes at least one of raw gypsum, desulfurized gypsum, phosphogypsum and fluorinated gypsum.

[0015] The suspending agent includes at least one of sodium carboxymethylcellulose, water-soluble polyvinyl alcohol or hydroxypropyl methylcellulose.

[0016] The water reducer includes at least one of a naphthalene-based water reducer, a melamine-based water reducer or a polycarboxylic acid-based water reducer.

[0017] The preparation method of the modified fiber is as follows: S1: Wash the fiber and dry it at 90-120°C for 2-5h; S2: placing the fiber obtained in step S1 in an acidic solution at a temperature of 40 to 90° C., immersing and ultrasonically vibrating the fiber for 30 to 60 minutes; S3: filtering out the fibers from step S2, drying them, and treating them with plasma for 2-10 minutes; S4: soaking the fiber obtained in step S3 in a solution containing a silane coupling agent for 10 to 30 minutes, washing, filtering, and drying to obtain the desired modified fiber.

[0018] The fiber comprises at least one of glass fiber, polyester fiber, polyamide fiber, polyvinyl alcohol fiber, polyacrylonitrile fiber, polypropylene fiber, polyvinyl chloride fiber, aluminum silicate fiber and basalt fiber, and the length of the fiber is 1 to 30 mm.

[0019] The acidic solution is at least one of dilute hydrochloric acid, dilute sulfuric acid, acetic acid, formic acid, propionic acid, organic boric acid, and organic phosphoric acid. There is no specific requirement for the concentration of the acidic solution, as long as the fiber surface can be etched.

[0020] The silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane. The concentration of the silane coupling agent solution is preferably 5-40%.

[0021] Plasma treatment is a commonly used method for surface modification, which is applicable to various reinforcement materials. It can generate free radicals, ions and metastable substances on the reinforcement surface, causing crosslinking and oxidation reactions. The surface modification effect of plasma treatment is remarkable. For example, oxygen plasma treatment can generate functional groups such as -COOH and C-OH on the fiber surface, while improving the wettability of the fiber, and the surface roughness is also significantly increased. The purpose of the present invention can be achieved by using oxygen plasma, nitrogen plasma, etc. commonly used in the art.

[0022] The fiber surface is etched by an acidic solution, and ultrasonic oscillation is used to relax the molecular chains in the fiber to create pores. The acidic solution can enter the pores and further etch the fiber surface, and part of it remains on the fiber surface. This treatment greatly increases the roughness and specific surface area of ​​the fiber surface, which is more conducive to the interaction between the silane coupling agent, plasma and fiber. At the same time, since some polar bonds remain on the fiber, it is also beneficial for the fiber to be evenly distributed in the binder, thereby improving the compressive strength after filling and reducing stress concentration inside the material, thereby improving the durability and reliability of the structure.

[0023] The present invention also provides a method for preparing a modified fiber mining filling material, comprising the following steps: Mix 35-75 parts of cement clinker, 10-20 parts of solid waste, 0.1-3 parts of retarder, 1-5 parts of early strength agent, 20-45 parts of modified fiber, 5-15 parts of accelerator, 10-20 parts of gypsum, 0.1-3 parts of water reducer and 0.5-5 parts of suspending agent evenly, add 100-600 parts of water and stir to obtain modified fiber mining filling material.

[0024] Compared with the prior art, the present invention has achieved the following beneficial effects: 1) The present invention utilizes the characteristics of early strength and fast hardening of cement clinker, and at the same time, by adding water reducing agent, early strength agent, retarder, etc., to ensure its fluidity, and has good fluidity within 30 minutes to meet the pouring requirements; it can quickly solidify and harden between 100 and 180 minutes, so that the filling material has better quick setting, early strength and other properties.

[0025] 2) The present invention significantly improves the dispersibility of fibers in filling materials by adopting dual modification technologies of plasma treatment and silane coupling agent. Plasma treatment can effectively change the properties of the fiber surface and increase its surface energy, while the silane coupling agent acts as a bridging agent to further promote the compatibility and bonding between the fiber and the binder. This synergistic effect effectively avoids fiber aggregation, thereby reducing stress concentration and improving the uniformity and integrity of the material. Through this modification, the filling material exhibits higher compressive strength and can maintain a high strength even when affected by the external environment, such as long-term immersion in water, that is, it has an excellent compressive strength retention rate. This not only enhances the stability and durability of the filling body, but also has important significance for improving the reliability and safety of mine support. In addition, the addition of modified fibers may also improve other properties of the filling material, such as crack resistance, toughness and overall mechanical properties, making it more adaptable to complex mining environments and engineering requirements.

[0026] 3) In the cement clinker system, the introduction of gypsum not only significantly improves the early compressive strength of the composite cementing material, but also ensures the long-term retention rate of strength, which is crucial to ensure the long-term stability of the filling body. In addition, the addition of gypsum also helps to adjust the setting time of cement clinker, ensuring the feasibility of construction operations and the timely hardening of filling materials.

[0027] 4) The preparation method of the modified fiber mining filling material of the present invention is simple and low in cost. The required filling material can be quickly prepared by simply stirring and mixing them at the application site. This method not only simplifies the on-site operation process, but also significantly reduces the preparation cost. In addition, the mixed filling material has good transportability and can be transported over long distances, greatly improving the engineering efficiency. At the same time, the environmental protection characteristics of the material are also in line with the current development trend of green mining, and have broad application prospects and important social and economic value. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only partial embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Example 1 The present embodiment provides a modified fiber mining filling material, the formula of which is: 50 parts of cement clinker, 10 parts of solid waste, 1 part of retarder, 2 parts of early strength agent, 25 parts of modified fiber, 10 parts of accelerating setting agent, 15 parts of gypsum, 1 part of water reducing agent, and 2 parts of suspending agent.

[0031] The cement clinker used in this embodiment is aluminate cement clinker, the solid waste is steel slag powder, the retarder is sodium gluconate, the early strength agent is calcium sulfate, the quick setting agent is sodium sulfate, the gypsum is desulfurized gypsum, the suspending agent is sodium carboxymethyl cellulose, and the water reducer is a polycarboxylic acid-based water reducer.

[0032] The preparation method of the modified fiber is as follows: S1: 25 g of 10 mm long polypropylene fiber was placed in 300 mL of anhydrous ethanol, ultrasonically cleaned for 15 min, and then dried at 100 °C for 3 h; S2: placing the polypropylene fiber obtained in step S1 in a dilute hydrochloric acid solution at a temperature of 50° C., immersing and ultrasonically vibrating for 60 minutes; S3: filtering out the fibers from step S2, drying them at 105°C, and treating them with oxygen plasma for 5 minutes; S4: Immerse the fiber obtained in step S3 in an ethanol solution of γ-aminopropyltriethoxysilane having a mass concentration of 30% for 20 minutes, wash and filter, and dry at 80° C. for 2 hours to obtain the desired modified polypropylene fiber.

[0033] The method for preparing the modified fiber mining filling material of this embodiment comprises the following steps: Weigh 50 parts of cement clinker, 10 parts of solid waste, 1 part of retarder, 2 parts of early strength agent, 25 parts of modified fiber, 10 parts of accelerating setting agent, 15 parts of gypsum, 1 part of water reducing agent and 2 parts of suspending agent, mix them evenly, add 200 parts of water and stir to mix evenly to obtain modified fiber mining filling material.

[0034] Example 2

[0035] The present embodiment provides a modified fiber mining filling material, the formula of which is: 70 parts of cement clinker, 15 parts of solid waste, 2 parts of retarder, 1 part of early strength agent, 35 parts of modified fiber, 5 parts of accelerating agent, 20 parts of gypsum, 0.5 parts of water reducing agent, and 3 parts of suspending agent.

[0036] The cement clinker used in this embodiment is a combination of sulphoaluminate cement clinker and ferroaluminate cement clinker in a ratio of 1:1, the solid waste is a mixture of fly ash and carbide slag in a ratio of 1:2, the retarder is borax, the early strength agent is a combination of calcium chloride and triethanolamine in a ratio of 1:1, the accelerator is sodium carbonate, the gypsum is raw gypsum, the suspending agent is water-soluble polyvinyl alcohol, and the water reducer is a naphthalene-based water reducer.

[0037] The preparation method of the modified fiber is as follows: S1: 15 g of aluminum silicate fiber with a length of 20 mm was placed in 200 mL of anhydrous ethanol, ultrasonically cleaned for 15 min, and then dried at 100 °C for 3 h; S2: placing the aluminum silicate fiber obtained in step S1 in an acetic acid solution at a temperature of 30° C., immersing and ultrasonically vibrating for 50 minutes; S3: filtering out the fiber from step S2, drying at 105°C, and treating with nitrogen plasma for 8 minutes; S4: Immerse the fiber obtained in step S3 in an ethanol solution of vinyltriethoxysilane having a mass concentration of 30% for 30 minutes, wash and filter, and dry at 100° C. for 1 hour to obtain the desired modified aluminum silicate fiber.

[0038] The method for preparing the modified fiber mining filling material of this embodiment comprises the following steps: Weigh 70 parts of cement clinker, 15 parts of solid waste, 2 parts of retarder, 1 part of early strength agent, 35 parts of modified fiber, 5 parts of accelerating agent, 20 parts of gypsum, 0.5 parts of water reducing agent and 3 parts of suspending agent, mix them evenly, add 300 parts of water and stir to mix evenly to obtain modified fiber mining filling material.

[0039] Example 3 The present embodiment provides a modified fiber mining filling material, the formula of which is: 35 parts of cement clinker, 20 parts of solid waste, 3 parts of retarder, 4 parts of early strength agent, 45 parts of modified fiber, 15 parts of accelerating setting agent, 15 parts of gypsum, 2 parts of water reducing agent, and 4 parts of suspending agent.

[0040] The cement clinker used in this embodiment is a combination of ferroaluminate cement clinker and fluoroaluminate cement clinker in a ratio of 2:1, the solid waste is a mixture of carbide slag and coal gangue in a ratio of 1:1, the retarder is a combination of borax and citric acid in a ratio of 2:1, the early strength agent is a combination of water glass and triethanolamine in a ratio of 1:1, the quick-setting agent is sodium aluminate, the gypsum is a combination of phosphogypsum and fluorgypsum in a ratio of 3:1, the suspending agent is hydroxypropyl methylcellulose, and the water reducer is a melamine water reducer.

[0041] The preparation method of the modified fiber is as follows: S1: 10 g of glass fiber with a length of 15 mm was placed in 200 mL of anhydrous ethanol, ultrasonically cleaned for 15 min, and then dried at 110 °C for 2 h; S2: placing the glass fiber obtained in step S1 in an organic boric acid solution at a temperature of 40° C., immersing and ultrasonically vibrating the solution for 40 minutes; S3: filtering out the fibers from step S2, drying them at 115° C., and treating them with oxygen plasma for 6 min; S4: Immerse the fiber obtained in step S3 in an ethanol solution of γ-glycidyloxypropyltrimethoxysilane having a mass concentration of 15% for 35 minutes, wash and filter, and dry at 110° C. for 1 hour to obtain the desired modified glass fiber.

[0042] The method for preparing the modified fiber mining filling material of this embodiment comprises the following steps: Weigh 35 parts of cement clinker, 20 parts of solid waste, 3 parts of retarder, 4 parts of early strength agent, 45 parts of modified fiber, 15 parts of accelerating setting agent, 15 parts of gypsum, 2 parts of water reducing agent and 4 parts of suspending agent, mix them evenly, add 350 parts of water and stir to mix evenly to obtain modified fiber mining filling material.

[0043] Example 4 The present embodiment provides a modified fiber mining filling material, the formula of which is: 65 parts of cement clinker, 15 parts of solid waste, 0.5 parts of retarder, 1 part of early strength agent, 25 parts of modified fiber, 5 parts of accelerating agent, 20 parts of gypsum, 3 parts of water reducing agent, and 5 parts of suspending agent.

[0044] The cement clinker used in this embodiment is a mixture of aluminate cement clinker and fluoroaluminate cement clinker in a ratio of 3:1, the solid waste is a mixture of copper slag powder and fly ash in a ratio of 2:1, the retarder is borax, the early strength agent is triethanolamine, the accelerator is sodium carbonate, the gypsum is a mixture of phosphogypsum and desulfurized gypsum in a ratio of 2:1, the suspending agent is hydroxypropyl methylcellulose, and the water reducer is a polycarboxylic acid water reducer.

[0045] The preparation method of the modified fiber is as follows: S1: 10 g of polyamide fiber with a length of 5 mm was placed in 200 mL of anhydrous ethanol, ultrasonically cleaned for 25 min, and then dried at 90 °C for 3 h; S2: placing the polyamide fiber obtained in step S1 in an organic phosphoric acid solution at a temperature of 40° C., immersing and ultrasonically vibrating for 30 minutes; S3: filtering out the fibers from step S2, drying them at 100° C., and treating them with oxygen plasma for 6 min; S4: Immerse the fiber obtained in step S3 in an ethanol solution containing γ-methacryloxypropyltrimethoxysilane at a mass concentration of 10% for 30 minutes, wash and filter, and dry at 110° C. for 1 hour to obtain the desired modified polyamide fiber.

[0046] The method for preparing the modified fiber mining filling material of this embodiment comprises the following steps: Weigh 65 parts of cement clinker, 15 parts of solid waste, 0.5 parts of retarder, 1 part of early strength agent, 25 parts of modified fiber, 5 parts of quick-setting agent, 20 parts of gypsum, 3 parts of water reducer and 5 parts of suspending agent, mix them evenly, add 300 parts of water and stir to mix evenly to obtain modified fiber mining filling material.

[0047] Example 5 The present embodiment provides a modified fiber mining filling material, the formula of which is: 55 parts of cement clinker, 20 parts of solid waste, 1 part of retarder, 2 parts of early strength agent, 35 parts of modified fiber, 10 parts of accelerating setting agent, 20 parts of gypsum, 2 parts of water reducing agent, and 4 parts of suspending agent.

[0048] The cement clinker used in this embodiment is fluoroaluminate cement clinker, the solid waste is fly ash, the retarder is borax, the early strength agent is calcium sulfate, the quick-setting agent is sodium carbonate, the gypsum is a combination of phosphogypsum and raw gypsum in a ratio of 2:1, the suspending agent is hydroxypropyl methylcellulose, and the water reducer is a polycarboxylic acid water reducer.

[0049] The preparation method of the modified fiber is as follows: S1: 15 g of 10 mm long polyvinyl alcohol fiber was placed in 200 mL of anhydrous ethanol, ultrasonically cleaned for 25 min, and then dried at 90 °C for 3 h; S2: placing the polyvinyl alcohol fiber obtained in step S1 in a dilute sulfuric acid solution at a temperature of 40° C., immersing and ultrasonically vibrating for 35 minutes; S3: filtering out the fibers from step S2, drying them at 100° C., and treating them with oxygen plasma for 5 min; S4: Immerse the fiber obtained in step S3 in an ethanol solution containing 35% vinyltriethoxysilane by mass for 30 minutes, wash and filter, and dry at 100° C. for 2 hours to obtain the desired modified polyvinyl alcohol fiber.

[0050] The method for preparing the modified fiber mining filling material of this embodiment comprises the following steps: Weigh 55 parts of cement clinker, 20 parts of solid waste, 1 part of retarder, 2 parts of early strength agent, 35 parts of modified fiber, 10 parts of quick-setting agent, 20 parts of gypsum, 2 parts of water reducer and 4 parts of suspending agent, mix them evenly in advance, add 400 parts of water, stir and mix evenly to obtain modified fiber mining filling material.

[0051] Example 6 The present embodiment provides a modified fiber mining filling material, the formula of which is: 65 parts of cement clinker, 20 parts of solid waste, 0.1 parts of retarder, 1 part of early strength agent, 30 parts of modified fiber, 5 parts of accelerating agent, 20 parts of gypsum, 3 parts of water reducing agent, and 5 parts of suspending agent.

[0052] The cement clinker used in this embodiment is ferroaluminate cement clinker, the solid waste is coal gangue, the retarder is borax, the early strength agent is calcium chloride, the quick setting agent is sodium sulfate, the gypsum is a combination of desulfurized gypsum and raw gypsum in a ratio of 1:1, the suspending agent is hydroxypropyl methylcellulose, and the water reducer is a polycarboxylic acid water reducer.

[0053] The preparation method of the modified fiber is as follows: S1: 20 g of 15 mm long polyvinyl chloride fiber was placed in 200 mL of anhydrous ethanol, ultrasonically cleaned for 25 min, and then dried at 100 °C for 2 h; S2: placing the polyvinyl chloride fiber obtained in step S1 in an acetic acid solution at a temperature of 40° C., immersing and ultrasonically vibrating for 30 minutes; S3: filtering out the polyvinyl chloride fiber from step S2, drying at 100° C., and treating with oxygen plasma for 5 min; S4: Immerse the polyvinyl chloride fiber obtained in step S3 in an ethanol solution of γ-aminopropyltriethoxysilane having a mass concentration of 10% for 30 minutes, wash and filter, and dry at 100° C. for 2 hours to obtain the desired modified polyvinyl chloride fiber.

[0054] The method for preparing the modified fiber mining filling material of this embodiment comprises the following steps: Weigh 65 parts of cement clinker, 20 parts of solid waste, 0.1 parts of retarder, 1 part of early strength agent, 30 parts of modified fiber, 5 parts of quick-setting agent, 20 parts of gypsum, 3 parts of water reducer and 5 parts of suspending agent, mix them evenly in advance, then add 300 parts of water and stir to mix evenly to obtain modified fiber mining filling material.

[0055] Example 7 Basalt fiber was used instead of the polypropylene fiber in Example 1, and other conditions were the same as those in Example 1.

[0056] Example 8 Polyacrylonitrile fiber was used instead of the polypropylene fiber in Example 1, and other conditions were the same as in Example 1.

[0057] Example 9 Polyester fiber was used instead of the polypropylene fiber in Example 1, and other conditions were the same as in Example 1.

[0058] Example 10 The length of the polypropylene fiber is 1 mm, and other conditions are the same as those in Example 1.

[0059] Embodiment 11 The length of the polypropylene fiber is 5 mm, and other conditions are the same as those in Example 1.

[0060] Example 12 The length of the polypropylene fiber is 15 mm, and other conditions are the same as those in Example 1.

[0061] Example 13 The length of the polypropylene fiber is 20 mm, and other conditions are the same as those in Example 1.

[0062] Embodiment 14 The length of the polypropylene fiber is 25 mm, and other conditions are the same as those in Example 1.

[0063] Embodiment 15 The length of the polypropylene fiber is 30 mm, and other conditions are the same as those in Example 1.

[0064] Comparative Example 1 The difference from Example 1 is that modified polypropylene fiber is not added, an equal amount of cement clinker is used instead of modified polypropylene fiber, and other conditions are the same as those in Example 1.

[0065] Comparative Example 2 The difference from Example 1 is that the polypropylene fiber is not modified, that is, the unmodified polypropylene fiber is used instead of the modified polypropylene fiber, and the other conditions are the same as those in Example 1.

[0066] Comparative Example 3 The difference from Example 1 is that the step of impregnating with S2 acid solution is omitted, and other conditions are the same as those in Example 1.

[0067] Comparative Example 4 The difference from Example 1 is that the step of S3 plasma treatment is omitted, and the silane coupling agent is used directly for modification after immersion in the acid solution. Other conditions are the same as those in Example 1.

[0068] Comparative Example 5 The difference from Example 1 is that the step of treating with S4 silane coupling agent is omitted, and the modified polypropylene fiber is obtained by impregnating with acid solution and then treating with plasma. The other conditions are the same as those in Example 1.

[0069] Comparative Example 6 The difference from Example 1 is that no gypsum is added, an equal amount of cement clinker is used instead of gypsum, and other conditions are the same as those in Example 1.

[0070] The properties of the modified fiber mining filling materials prepared in this embodiment and the comparative example are shown in Table 1. The stirred slurry was injected into a 40mm×40mm×160mm triple mold, and after curing at room temperature of 25°C for 48 hours, the material was demoulded and cut, and the compressive strength, longitudinal expansion rate and other properties of the material were tested after the material was dried. The initial setting time and final setting time of the material were tested in accordance with the "Standard for Test Methods for Properties of Ordinary Concrete Mixtures" (GB / T50080-2016); the compressive strength was tested using "JC / T984-2011"; the vertical expansion rate was referenced to Appendix C of GB 50119-2003.

[0071] Retention rate of compressive strength: Take the specimen to test the compressive strength, recorded as M1, then soak the specimen in water for 72 hours and then test the compressive strength, recorded as M2. The retention rate of compressive strength = M2 / M1*100.

[0072] Table 1 Filling material properties of different embodiments and control examples

[0073] It can be seen from the performance test in Table 1 that the modified fiber mining filling material prepared in the embodiment of the present invention has good fluidity within 30 minutes, can quickly solidify and harden between 100 and 180 minutes, and the filling material has better quick-setting, early strength and other properties; the dual modification technology of plasma treatment and silane coupling agent is adopted to significantly improve the dispersion of fibers in the filling material, the compressive strength retention rate of the material is more than 98%, and the expansion rate is less than 4%, which not only enhances the stability and durability of the filling body, but also has important significance for improving the reliability and safety of mine support, making it more adaptable to complex mining environment and engineering requirements.

[0074] From the comparison of Examples 1 and 10-15, it can be seen that in the filling material, the length of the fiber has a certain influence on the compressive strength retention rate of the filling material. Different fiber lengths affect the dispersion of the fiber in the filling material, and can more effectively combine with the material matrix to form more anchor points, thereby improving the overall compressive strength retention rate of the filling material.

[0075] Compared with Example 1, no modified fiber was added to Example 1, and unmodified fiber was used in Example 2. The compressive strength retention rate of the filling material was significantly reduced. The present invention adopts a dual modification technology of plasma treatment and silane coupling agent, which significantly improves the dispersion of the fiber in the filling material. Plasma treatment can effectively change the properties of the fiber surface and increase its surface energy, while the silane coupling agent acts as a bridging agent to further promote the compatibility and adhesion between the fiber and the binder. Even under the influence of the external environment, such as long-term immersion in water, it can maintain a high strength, that is, it has an excellent compressive strength retention rate, which enhances the stability and durability of the filling body.

[0076] Compared with Example 1, Example 3 did not use an acidic solution to etch the surface, Example 4 omitted the S3 plasma treatment step, and Example 5 omitted the S4 silane coupling agent treatment step. The compressive strength retention rate of the filling materials in Examples 3-5 decreased significantly, and the expansion rate increased significantly, which was due to the decreased compatibility between the fiber and the binder.

[0077] By comparing Example 1 with Comparative Examples 1-5, it can be found that the initial setting time of the filling material using the modified fiber in the present invention has no significant change, but the final setting time is significantly shortened, indicating that the modified fiber can accelerate the hardening process of the filling material, thereby improving the construction efficiency and the early use performance of the material. This also means that in actual engineering applications, subsequent construction or use can be carried out earlier, further optimizing the construction process and time arrangement.

[0078] The comparative analysis of Example 1 and Comparative Example 6 reveals that the synergistic effect of the modified fiber and gypsum in the present invention significantly improves the performance of the filling material. This combination not only effectively improves the compressive strength retention rate of the material, but also reduces the expansion rate of the material. This improvement helps to enhance the stability and durability of the filling material, especially in application scenarios under high pressure or in dynamic environments. Through this optimization, the filling material can better adapt to different geological conditions and engineering requirements, and improve its applicability and reliability in actual engineering.

[0079] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A modified fiber mining filling material, characterized in that: The material comprises the following raw materials in parts by weight: 35-75 parts of cement clinker, 10-20 parts of solid waste, 0.1-3 parts of retarder, 1-5 parts of early strength agent, 20-45 parts of modified fiber, 5-15 parts of accelerating agent, 10-20 parts of gypsum, 0.1-3 parts of water reducing agent, and 0.5-5 parts of suspending agent; The preparation method of the modified fiber is as follows: S1: Wash the fiber and dry it at 90-120°C for 2-5h; S2: placing the fiber obtained in step S1 in an acidic solution at a temperature of 40 to 90° C., immersing and ultrasonically vibrating the fiber for 30 to 60 minutes; S3: filtering out the fibers from step S2, drying them, and treating them with plasma for 2-10 minutes; S4: soaking the fiber obtained in step S3 in a solution containing a silane coupling agent for 10 to 30 minutes, washing, filtering, and drying to obtain the desired modified fiber.

2. The modified fiber mining filling material according to claim 1, characterized in that: The cement clinker includes at least one of aluminate cement clinker, sulphoaluminate cement clinker, ferroaluminate cement clinker and fluoroaluminate cement clinker.

3. The modified fiber mining filling material according to claim 1, characterized in that: The solid waste includes at least one of steel slag powder, copper slag powder, fly ash, carbide slag and coal gangue.

4. The modified fiber mining filling material according to claim 1, characterized in that: The retarder includes at least one of sodium gluconate, borax or citric acid; the early strength agent includes at least one of calcium chloride, calcium sulfate, water glass or triethanolamine; the quick setting agent includes at least one of sodium aluminate, sodium sulfate or sodium carbonate.

5. The modified fiber mining filling material according to claim 1, characterized in that: The gypsum includes at least one of raw gypsum, desulfurized gypsum, phosphogypsum and fluorinated gypsum.

6. The modified fiber mining filling material according to claim 1, characterized in that: The fiber includes at least one of glass fiber, polyester fiber, polyamide fiber, polyvinyl alcohol fiber, polyacrylonitrile fiber, polypropylene fiber, polyvinyl chloride fiber, aluminum silicate fiber, and basalt fiber, and the fiber length is 1 to 30 mm; the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.

7. The modified fiber mining filling material according to claim 1, characterized in that: The suspending agent includes at least one of sodium carboxymethylcellulose, water-soluble polyvinyl alcohol or hydroxypropyl methylcellulose.

8. The modified fiber mining filling material according to claim 1, characterized in that: The water reducer includes at least one of a naphthalene-based water reducer, a melamine-based water reducer or a polycarboxylic acid-based water reducer.

9. A method for preparing a modified fiber mining filling material according to any one of claims 1 to 8, characterized in that: Mix 35-75 parts of cement clinker, 10-20 parts of solid waste, 0.1-3 parts of retarder, 1-5 parts of early strength agent, 20-45 parts of modified fiber, 5-15 parts of accelerator, 10-20 parts of gypsum, 0.1-3 parts of water reducer and 0.5-5 parts of suspending agent evenly, add 100-600 parts of water and stir to obtain modified fiber mining filling material.

10. An application of the modified fiber mining filling material according to any one of claims 1 to 8 in mine filling and support, characterized in that: The formed filling material is transported to the area of ​​the mine that requires filling support.

Citation Information

Patent Citations

  • Application of polypropylene fiber-containing cemented filling material to filling mining

    CN107500634A

  • Quick-setting filling cementing material

    CN111072296A

  • Aramid fiber for reinforcing concrete and method for manufacturing the same

    KR1020130063900A

  • Personalized Brain Map Generation Method and Apparatus therefor

    KR1020250031478A

Cited By

  • Concrete for waste fiber water net engineering

    CN120117859A

  • Low-clinker cement activator

    CN122145062A

  • Quick-setting admixture for mining filling and plugging material and preparation method of quick-setting admixture

    CN122145068A